2019
DOI: 10.1186/s11671-019-2974-2
|View full text |Cite
|
Sign up to set email alerts
|

A Ternary Magnetic Recyclable ZnO/Fe3O4/g-C3N4 Composite Photocatalyst for Efficient Photodegradation of Monoazo Dye

Abstract: To develop a highly efficient visible light-induced and conveniently recyclable photocatalyst, in this study, a ternary magnetic ZnO/Fe 3 O 4 /g-C 3 N 4 composite photocatalyst was synthesized for the photodegradation of Monas dye. The structure and optical performance of the composite photocatalyst were characterized using X-ray diffraction (XRD), transmission electron microscopye (TEM), energy dispersive spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(14 citation statements)
references
References 34 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Table 4 illustrates the photocatalytic performance of our Fe 2 O 3 -zeolite photocatalyst comparing with the previously studied metal oxide and/or zeolite-based photocatalysts for MB dye degradation [46][47][48][49][50][51][52][53]. As shown in this table, the presented photocatalytic performance parameters are much higher than the reported performances for the previously reported catalysts in the literature.…”
Section: Kinetics Of Photocatalytic Processmentioning
confidence: 81%
“…Table 4 illustrates the photocatalytic performance of our Fe 2 O 3 -zeolite photocatalyst comparing with the previously studied metal oxide and/or zeolite-based photocatalysts for MB dye degradation [46][47][48][49][50][51][52][53]. As shown in this table, the presented photocatalytic performance parameters are much higher than the reported performances for the previously reported catalysts in the literature.…”
Section: Kinetics Of Photocatalytic Processmentioning
confidence: 81%
“…The obtained results from GAF spectra (Figure 2e) displayed that the mass ratio of CGNS, Ag 2 O, and α-Fe 2 O 3 nanoparticles are nearly 3, 2, and 1, respectively. [36,37] The uniform distribution of elements was observed in the elemental mapping analysis on the GAF nanocomposite (Figure 3).…”
Section: Introductionmentioning
confidence: 90%
“…The addition of porous ruthenium further decreased the PL intensity, which indicated that the g-C 3 N 4 / Fe 3 O 4 /p-RuNP nanocomposite had a much lower recombination rate of the photo-induced electron-hole pairs compared to those in the pristine g-C 3 N 4 nanosheet and g-C 3 N 4 / Fe 3 O 4 NP. 41,49,61,[88][89][90][91][92] Photocatalytic activity towards the removal of aromatic amines…”
Section: Synthesis and Characterisationmentioning
confidence: 99%